Information and communications technology (ICT) and international trade: evidence from Turkey - Ozcan, Burcu (Springer Heidelberg, 2018)
This study analyzes the impacts of information and communications technology (ICT) on international trade between Turkey and its trading partners. Using an extended panel gravity model framework, it examines the effects of four ICT indices on Turkish bilateral exports and imports with static and dynamic panel data models for the period 2000-2014. The sample includes 35 countries that import Turkish goods and 34 countries that export goods to Turkey. The results indicate that ICT has positive and significant impacts on both Turkish import and export volumes. Additionally, ICT has a quantitatively larger effect on imports than on exports. These results are robust to alternative model specifications and estimation methods. Based on these results, some policy implications can be derived. For instance, Turkey may develop strategic trading partnerships with countries that have achieved high levels of ICT development, in order to increase its overall trade.
Keywords: Information and communications technology; International trade; Trade costs; Gravity model; Panel data models; Turkey